Understanding the basics of electrotherapy, Glavnotherapy, Electrophoresis, Darsonvalization (Texas Journal of Medical Science, 2025)
The article discusses the methods of electrotherapy treatment with Glavnotherapy, Electrophoresis and Dorsonvalization in diseases such as neuralgia, vasculitis, diseases of the nervous system, rheumatism of the joints, neurasthenia.